Annotated record of the detailed examination of Mn deposits from DSDP Site 74, Leg 8 (Core 74-12) - Tracey, J I; Sutton, George H; Nesteroff, Wladimir D; Galehouse, J S; von der Borch, Christopher C; Moore, T; Lipps, J; Haq, Bilal U; Beckmann, Jean-Pierre (Supplement to: Tracey, JI et al. (1971): Site 74. In: Tracey, J.I.Jr.; et al., Initial Reports of the Deep Sea Drilling Project, 8, Initial Reports of the Deep Sea Drilling Project, U.S. Government Printing Office, VIII, 621-674, https://doi.org/10.2973/dsdp.proc.8.109.1971, 1971)
Site 74 is located 250 miles northeast of the Marquesas Islands and lies 270 miles south of Site 73 and 400 miles north of Site 75. It is one of the sites along the N-S line drilled during Leg 8 to investigate the east-west trending accumulation of sediments centered about 2°N near 140°W. Site 74 is located near the center of a relatively flat area about 3 miles across. There is some indication of minor deformation at the site.